The PALliative MUlticenter Study in Intensive Care (PalMuSIC). Results From a Multicenter Study Addressing Frailty and Palliative Care Interventions in Intensive Care Units in Portugal - Correia, Iuri (2021)
Objective: Frailty is a clinically recognizable state of increased vulnerability common in critical medicine. When underrecognized, it may lead to invasive treatments that do not serve the patients’ best interest. Our aim was to evaluate the use of both palliative care consultation and invasive interventions in frail patients admitted to Intensive Care Units in Portugal. Methods: This was a prospective, observational study. All consecutive adult patients admitted for more than 24h, over a 15-day period were enrolled. Twenty-three Portuguese Intensive Care Units were included. Informed consent was obtained from all patients or their surrogate. The doctor and nurse in charge calculated the Clinical Frailty Score as well as the reference family member Results: A total of 335 patients were included in the study (66% male). Mean age was 63.2 + 16.8 and SAPS II score was 41.8 + 17.4. Mean Clinical Frailty Score value was 3.5 + 1.7. Frailty prevalence (mean score 5) was 20.9%. Frail patients were offered organ support therapy (64,3% invasive mechanical ventilation; 24,3% renal replacement therapy; 67,1% vasopressors) more often than non-frail patients. Nevertheless, limitation of therapeutic effort or a do not resuscitate order (p < 0.001) were more common in frail patients. Mortality rate by 6 months was higher among frail patients (50% vs. 32.3%, p < 0.001). Palliative Care was offered to only 15% of frail patients (3.9% overall). Conclusions: The authors suggest that palliative care should be universally consulted once frailty is identified in critical patients.